The Impact Of Convergence Of International Accounting Standards (IFRS) On The Quality Of Financial Reports: Meta-Analysis - Zufi Yustika Magitasiwi; Anindya Frysa Irsyadi; Hwihanus Hwihanus (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
This research uses qualitative meta-analysis to examine the impact of implementing International Financial Reporting Standards (IFRS) on the financial quality of companies. This meta-analysis examines 6 empirical studies that examine the relationship between IFRS and financial reporting quality. The meta-analysis results show that the implementation of IFRS has a significantly improves the quality of financial reporting, promoting transparency, accountability and better decision making.